2017
DOI: 10.1093/ehjci/jex163
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional right-ventricular regional deformation and survival in pulmonary hypertension

Abstract: Right ventricular strain patterns gradually worsen in PH patients and provide independent prognostic information in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 44 publications
4
84
0
2
Order By: Relevance
“…A similar response can be recognized in patients with pulmonary arterial hypertension, and the prognostic value of this phenomenon is well established. 24,25 Post-operative shift in right ventricular contraction pattern…”
Section: Adaptation To Chronic Primary Mitral Valve Regurgitationmentioning
confidence: 99%
“…A similar response can be recognized in patients with pulmonary arterial hypertension, and the prognostic value of this phenomenon is well established. 24,25 Post-operative shift in right ventricular contraction pattern…”
Section: Adaptation To Chronic Primary Mitral Valve Regurgitationmentioning
confidence: 99%
“…have shown that longitudinal strain measured from the entire RV fee wall correlates well with RV contractile function while the novel study from Moceri et al. found that right ventricular strain patterns worsen in pulmonary hypertension patients and provide independent prognostic information in that population …”
Section: Discussionmentioning
confidence: 99%
“…At present, most of the data in this area has investigated global longitudinal strain [15][16][17][18][19]. Area strain, a measure of relative area change that incorporates longitudinal and circumferential strain, holds promise as a useful clinical tool [20].…”
Section: Right Ventricular Systolic Functionmentioning
confidence: 99%